2016
DOI: 10.1111/nmo.12921
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization toward irritable bowel syndrome and inflammatory bowel disease in an online cohort

Abstract: Background Stigma is associated with many negative health outcomes. Research has examined perceived and internalized stigma in individuals with irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD), but less has been done to evaluate levels of enacted stigma associated with these conditions. The aim of this study was to evaluate the presence of enacted stigma toward IBS and IBD in the general population compared to an adult-onset asthma (AOA) control group. Methods Participants were recruited v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 56 publications
1
24
1
Order By: Relevance
“…pouch that allows bodily waste to enter through the abdominal wall), indicating stronger stigmatising attitudes towards those with this condition. Another study (Taft et al, 2017) also found that a community sample indicated the highest level of enacted stigmatisation towards men with Irritable Bowel Syndrome (IBS), compared to other chronic conditions. IBS shares similar symptoms to IBD (e.g.…”
Section: Community Perceptions Of Ibdmentioning
confidence: 98%
See 3 more Smart Citations
“…pouch that allows bodily waste to enter through the abdominal wall), indicating stronger stigmatising attitudes towards those with this condition. Another study (Taft et al, 2017) also found that a community sample indicated the highest level of enacted stigmatisation towards men with Irritable Bowel Syndrome (IBS), compared to other chronic conditions. IBS shares similar symptoms to IBD (e.g.…”
Section: Community Perceptions Of Ibdmentioning
confidence: 98%
“…Whilst few studies have examined societal perceptions of IBD, societal perceptions have been the focus of attention for other conditions (Anagnostopoulos & Spanea, 2005;Kouznetsova, Stevenson, Oaten, & Case, 2012;Smith et al, 2007;Taft, Bedell, Naftaly, & Keefer, 2017). For example, literature suggests that the general population demonstrates negative, stigmatising attitudes towards those with infectious conditions such as human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/ AIDS; Huskin, Reiser-Robbins, & Kwon, 2018;Katz et al, 1987;Mak et al, 2006), severe acute respiratory syndrome (SARS; Lau, Yang, Wong, & Tsui, 2006) and tuberculosis (TB; Baral, Karki, & Newell, 2007).…”
Section: Community Perceptions Of Ibdmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2016 comprehensive review of IBD stigma finds IBD patients perceive that others hold stigmatizing views toward them and the disease, some patients internalize these negative beliefs while others resist them, and stigmatizing attitudes and behaviors exist among those without IBD 59, 60 . Like stigma toward other diseases, IBD stigma is associated with poorer outcomes 61 and may cause or exacerbate feelings of depression or anxiety.…”
Section: Stigmamentioning
confidence: 99%